Fractal dimension of random invariant sets for nonautonomous random dynamical systems and random attractor for stochastic damped wave equation. (March 2016) - Zhou, Shengfan; Zhao, Min
Abstract: In this paper, we first establish a criteria for estimating the upper bound of fractal dimension of a random compact invariant set of a non-autonomous random dynamical system on a separable Banach space and give some special conditions which can be easily verified to some stochastic partial differential equations for bounding the fractal dimension of random attractors. Then we apply these conditions to obtain an upper bound of fractal dimension of random attractor for stochastic damped wave equation with additive white noise.